STRATEGIES IN THE IMPLEMENTATION OF SYNCHROMODAL FREIGHT TRANSPORTATION ON SUMATERA ISLAND - Setijadi, Setijadi; Hartati, Verani; Fauzi, Muchammad (LPPM Universitas Bina Bangsa, 2024)
The Sumatra region plays a significant role in Indonesia's economy. In 2022, for instance, the region contributed 22.04% to Indonesia's Gross Domestic Product (GDP), ranking just below Java, the largest contributor. Sumatra is rich in various resources such as plantations, oil, gas, and geothermal energy. However, the operational activities of freight transportation in Sumatra, particularly West Sumatra, still face several challenges stemming from the transportation system and environmental conditions. This research was conducted to explore the opportunities, challenges, strengths, and weaknesses of implementing a synchromodal transportation system in Sumatra as an analysis for its implementation. The study used the Synchromodality Framework and SWOT Analysis. Several transportation collaboration models have been developed, including unimodality, intermodality, multimodality, and synchromodality. Each model has its advantages and disadvantages and is applied based on the characteristics of the transportation system. Related studies have been conducted on multimodal transport, hub & spoke for regional transportation, and single-mode transport. The study concluded that the advantages of implementing a synchromodal transportation system in Sumatra include better utilization of available resources concerning real-time aspects, flexibility, collaboration and coordination, and synchronization. Its weaknesses are related to the need for collaboration networks among transportation operators from different business sectors. The opportunities for implementing synchromodal transportation in Sumatra include real-time aspects, flexibility, collaboration and coordination, synchronization, and commodity and regional factors. The challenges relate to the complexity of planning synchromodal transportation networks and routes, as well as the need for technological and information system support